The right of citizens for public legal initiatives in the Republic of Belarus: theory and practice - Kisialiova, Tatsiana M. (Journal of the Belarusian State University. Law, 2025)
The author of the article reveals the essence and features of realisation of the right for public legal initiatives in the Republic of Belarus. The recognition of the right for public legal initiatives as an independent element of the right to manage the affairs of the state is substantiated. The author identifies certain problems of the realisation of the right for public legal initiatives and suggests the ways to solve them.
Keywords: public legal initiatives; right for public legal initiatives; right to participate in the management of public affairs; right of petition; civic initiatives